Character and rhetoric ín proper names ín spanísh romances of chivalry - Marín Pina, María del Carmen (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Onomastics is an indispensible element in the configuration of the chivalrous personality and in the development of his various adventures. An analysis and interpretation of proper names will reveal the essence of the various characters, their qualities and their states of mind. A study of the mechanisms and principIes governing their formation (etymological invention and derivation of names) also shows that in the tales of chivalrous deeds, the name itself is a fascinating verbal adventure.